Sammlung "Junge Kunst". (Duisburg : König-Brauerei, 1975)
Abrahams, Ivor ; Agam, Yaakov ; Alt, Otmar ; Antes, Horst ; Bak, Imre ; Barge, Michael Jens ; Bayrle, Thomas ; Berges, Werner ; Berner, Bernd ; Brüning, Peter ; Damke, Bernd ; Dine, Jim ; Dossi, Ugo ; Fijalkowski, Stanislaw ; Filliou, Robert ; Frenken, Wil ; Freyer, Achim ; Geiger, Rupprecht ; etc.
boek